A comparative study of manganese–cerium doped metal–organic frameworks prepared via impregnation and in situ methods in the selective catalytic reduction of NO. Issue 10 (17th January 2017) - Zhang, Xiao; Shen, Boxiong; Zhang, Xiaoqi; Wang, Fumei; Chi, Guilong; Si, Meng
Abstract : Impregnation and in situ doping were applied for the preparation of MnCe loaded MOFs and the behavior of the catalysts in the SCR was investigated. Abstract : Mn and Ce were loaded on metal–organic frameworks (MOFs) via impregnation and in situ doping methods. The catalytic capacities of the obtained composite materials were evaluated in the selective catalytic reduction (SCR) of NO. The existing form of Mn–Ce in the MOF originates from different doping methods and its effect on the catalytic performance was investigated. Mn–Ce introduced by impregnation was deposited on the surface of the MOF and exhibited high catalytic efficiency of more than 98% from 200 °C to 300 °C. According to the results of BET, XRD, XPS, and ICP analyses, it was concluded that Mn–Ce introduced via the in situ doping method was inserted in the crystal lattice structure of the MOF, which resulted in an enlarged surface area, low Mn concentration, and poor redox property as compared to that introduced via the impregnated method. By exploring these factors, it was proven that the limited redox ability was the direct reason that resulted in the low activity of the MnCeMOF. Using thermal decomposition, the in situ doped Mn–Ce was liberated from the MnCeMOF crystal lattice and subsequently, exhibited recovered redox properties and catalytic activity. In this study, we proved that different doping methods lead to different forms of Mn–Ce in the MOF, which exhibit different redox properties and thus directly lead to different catalytic performance.